Nursing care in the prevention of pneumonia associated with mechanical ventilation: Integrative review (Research, Society and Development, 2024)
Mechanical Ventilator-Related Pneumonia (PVAM) is characterized as a lung infection that develops after endotracheal intubation and the start of invasive mechanical ventilation. It initially occurs within 48 to 72 hours of hospital stay. In the intensive care unit, PVAM is the most frequently observed contamination, with an incidence ranging from 9% to 27% among patients undergoing endotracheal intubation. The objective of the work was to identify the preventive strategies adopted by nursing professionals in managing PVAM and analyze the team's behavior in light of the prevention criteria for this condition. This is an integrative review of the literature in which data collection was carried out through an active search in scientific articles in virtual libraries. According to the inclusion and exclusion criteria, 35 articles were selected, grouped into two distinct categories, namely: Pneumonia Associated with Mechanical Ventilation and nursing interventions and the other, adherence and knowledge about bundles for VAP prevention. In a comprehensive way, it was observed through the analyzes carried out that there is insufficient adherence to VAP prevention bundles, accompanied by limited knowledge on the part of nursing professionals in relation to such measures. In this context, the relevance of this study lies in the need to raise awareness among nursing professionals, leading them to reflect on the true purpose of health-related infection prevention practices, thus promoting improvement in the quality of services provided and ensuring safety of the patient.